When Are Real Options Exercised? An Empirical Study of Mine Closings - Moel, Alberto; Tufano, Peter (Review of Financial Studies, 2002)
Journal Article When Are Real Options Exercised? An Empirical Study of Mine Closings Get access Alberto Moel, Alberto Moel Monitor Corporate Finance, Monitor Group Address correspondence to Peter Tufano, Harvard Business School, Morgan Hall, Soliders Field, Boston, MA 02163, or e-mail: ptufano@hbs.edu. Search for other works by this author on: Oxford Academic Google Scholar Peter Tufano Peter Tufano Harvard Business School and NBER Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 15, Issue 1, January 2002, Pages 35–64, https://doi.org/10.1093/rfs/15.1.35 Published: 16 June 2015